EFICÁCIA DE DIFERENTES PRODUTOS NO DESENTUPIMENTO DOS GOTEJADORES NUM SISTEMA DE REGA GOTA-A-GOTA - Salgueiro, João; Paulo, Ana (Revista da UI_IPSantarém, 2018)
The objective of this experiment is to test and compare the efficacy of phosphoric acid, nitric acid, and two commercial products, Oxi Premium 15 and Sulfacid, in cleaning the emitters of a drip irrigation system installed in a superintensive olive orchard located near Santarém. In the experiment the total of 80 emitters in four irrigation sectors were selected, 20 in each sector. Water volumetric samples of their flow were collected for 1 minute. The samples were collected before and after the product has been applied, making a total of 160 samples. The emitter performance and the efficacy of the cleaning products were evaluated using the coefficient of variation of emitter discharge (cv), the uniformity coefficient (UD), and the percentage of emitter clogging, before and after the emitter cleaning. The statistical analysis concerns the difference of discharge before and after the product has been applied. The mean, the standard deviation and the confidence intervals for the discharge difference was assessed. The number of emitters that have reached the maximum discharge rate (50 mL/min.) was recorded. The final results are not completely conclusive regarding the comparison between products, however it is observed that nitric acid and Oxi Premium 15 are the most effective in the cleaning of drippers and irrigation piping. Sulfacid is the product with the least satisfactory results.